Enhancing efficiency of low-grade heat harvesting by structural vibration entropy in thermally regenerative electrochemical cycles - Choi, Ahreum (2023)
The majority of waste-heat energy exists in the form of low-grade heat (<100 °C), which is immensely difficult to convert into usable energy using conventional energy-harvesting systems. Thermally regenerative electrochemical cycles (TREC), which integrate battery and thermal-energy-harvesting functionalities, are considered an attractive system for low-grade heat harvesting. Herein, the role of structural vibration modes in enhancing the efficacy of TREC systems is investigated. How changes in bonding covalency, influenced by the number of structural water molecules, impact the vibration modes is analyzed. It is discovered that even small amounts of water molecules can induce the A1g stretching mode of cyanide ligands with strong structural vibration energy, which significantly contributes to a larger temperature coefficient (ɑ) in a TREC system. Leveraging these insights, a highly efficient TREC system using a sodium-ion-based aqueous electrolyte is designed and implemented. This study provides valuable insights into the potential of TREC systems, offering a deeper understanding of the intrinsic properties of Prussian Blue analogs regulated by structural vibration modes. These insights open up new possibilities for enhancing the energy-harvesting capabilities of TREC systems.